2022
DOI: 10.3390/v14112507
|View full text |Cite
|
Sign up to set email alerts
|

Insights on 21 Years of HBV Surveillance in Blood Donors in France

Abstract: Hepatitis B virus (HBV) infection is the most frequent viral infection found in blood donors (BDs) in France. We analyzed the epidemiological and sero-molecular data on HBV infection gathered over the past two decades by the French haemovigilance surveillance network, blood screening laboratories, and the national reference center for transfusion infectious risks (NRC). Between 2000 and 2020, 6149 of the 58,160,984 donations (1.06/10,000) tested HBV positive, 98% of them from first-time blood donors (FTBDs). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…19 In addition, the HCV-antibody positive/ RNA negative profile may have a viral load that is below the level of detection. Cappy et al 20 estimated that approximately 0.5% of HCV-antibody positive but NAT negative blood donations in France had low HCV RNA levels. Groves et al 21 reported that low-level HCV-RNA reactivity is decreasing over time from 0.34% to 0.1%, perhaps due to the widespread use of highly effective direct-acting antiviral treatments of HCV infection in USA.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, the HCV-antibody positive/ RNA negative profile may have a viral load that is below the level of detection. Cappy et al 20 estimated that approximately 0.5% of HCV-antibody positive but NAT negative blood donations in France had low HCV RNA levels. Groves et al 21 reported that low-level HCV-RNA reactivity is decreasing over time from 0.34% to 0.1%, perhaps due to the widespread use of highly effective direct-acting antiviral treatments of HCV infection in USA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the last D.N-1 that was retrospectively found to be HBV-DNA positive despite screening HBV-DNA negative was collected in 2019 from a donor with an HBc Ab negative occult B infection. Due to the donor's donation history, this case, described in detail elsewhere, was extensively investigated [4].…”
Section: Lookback Studiesmentioning
confidence: 99%
“…At the same time, the HCV epidemic remains high and uncontrolled in France, with a high HCV infection prevalence among PWID that reached 64% in 2011 compared to 74% in 2004 [6]. Previous studies conducted in 2011 also show that HCV incidence is very high (20%) among PWID [7]: much higher compared to the general population (estimated among blood donors at one in 34 million donations) [8]. Indeed, France was late in implementing a national harm reduction policy compared to other countries such as the Netherlands and Switzerland, that were able to rapidly control HCV infections among PWID [9–11].…”
Section: Introductionmentioning
confidence: 99%